A homological version of a result of digital topology - Kong, T. Yung (Topology Proceedings, 2023)
Let $\mathcal{F}$ be any collection of subspaces of a topological space and let $\mathcal{D} \subseteq \mathcal{F}$. We say $\mathcal{D}$ is homology-simple in $\mathcal{F}$ if the inclusion map of $\cup(\mathcal{F} \backslash \mathcal{D})$ in $\cup \mathcal{F}$ induces homology group isomorphisms in all dimensions, and say $\mathcal{D}$ is hereditarily homology-simple in $\mathcal{F}$ if every subcollection of $\mathcal{D}$ is homology-simple in $\mathcal{F}$. Thinning algorithms are used in image processing to simplify binary images. An $n D$ binary image may be regarded as a representation of a finite collection of closed $n$-cubes that are grid cells of an $n D$ Cartesian grid. Then the goal of thinning is to reduce such a collection of grid cells to a subcollection that is a "thin skeleton" of the collection. Thinning algorithms are commonly designed in such a way that, if $\mathcal{J}_{\text {in }}$ is the original collection of grid cells and $\mathcal{J}_{\text {skel }}$ the resulting skeleton, then $\mathcal{F}_{\text {in }} \backslash \mathcal{F}_{\text {skel }}$ is homology-simple in $\mathcal{F}_{\text {in }}$. We call this the homology preservation condition. For $n \in\{2,3,4\}$, a theorem of Bertrand and Couprie implies a local characterization of the hereditarily homology-simple subcollections of any finite collection $\mathcal{F}$ of $n D$ Cartesian grid cells. The theorem and the implied characterization of hereditary homologysimpleness can be used to design good parallel thinning algorithms that automatically satisfy the homology preservation condition, and can also be useful for verifying that a proposed parallel thinning algorithm satisfies that condition. Bertrand and Couprie's work makes no explicit use of homology. It is based on collapsing of complexes and depends on $\mathcal{F}$ being part of a cubical complex of dimension $≤ 4$. This paper shows how their theorem can be restated using homology, and shows that the restated theorem is valid under much weaker hypotheses than were assumed in the original theorem. For example, it is valid whenever $\mathcal{F}$ is a finite collection of acyclic polyhedra in $\mathbb{R}^n$ whose nonempty intersections are acyclic, and whenever $\mathcal{F}$ is a finite collection of acyclic open sets (of any topological space) whose nonempty intersections are acyclic. We also deduce a characterization of hereditary homology-simpleness in the case where $\mathcal{F}$ is a finite collection of singleton subspaces of Khalimsky $n$-space.